An investigation of JAK2 mutation in patients with ulcerative colitis with a history of thrombosis: JAK2 mutation and ulcerative colitis - Buran, Tahir; Batır, Muhammet Burak; Çam, Fethi Sırrı; Kasap, Elmas (Journal of Surgery and Medicine, 2023)
Background/Aim: JAK2 is a gene that provides instructions for making a protein called Janus kinase 2, which is involved in the signaling process that regulates the growth and division of cells. Variations in the JAK2 gene have been associated with several different diseases, including certain blood disorders like myeloproliferative neoplasms (MPNs) and ulcerative colitis (UC). The exact reason for ulcerative colitis is not fully understood. This study aimed to examine the possible role of JAK2 V617F mutation in the etiopathogenesis of ulcerative colitis. Methods: The included patients were selected with UC and with signs of thrombosis. The DNA isolation was carried out from peripheral blood for all included patients. RT-qPCR methods were used to find JAK2 V617F mutations in UC patients with signs of thrombosis. Results: 73.3% of the included patients in this study had bloody diarrhea and 80% had abdominal pain. Also, the JAK2 V617F mutation rate was detected in 6.6% of the patients included in the study. Conclusion: In this study, it was found that the V617F mutation was relatively rare in ulcerative colitis patients and there was no correlation with the JAK2 V617F mutation in most of the ulcerative colitis cases with thrombotic symptoms.